Lubiprostone in constipation: clinical evidence and place in therapy. (March 2015) - Wilson, Nicholas; Schey, Ron
Constipation is one of the most common function bowel disorders encountered by primary care providers and gastroenterologists. Disorders of chronic constipation, including irritable bowel syndrome with constipation, chronic idiopathic constipation, and opioid-induced chronic constipation, are associated with significant medical costs and a negative impact on quality of life. Although there is evidence supporting the effectiveness of some over-the-counter laxatives in chronic constipation, currently there is no evidence supporting lifestyle modification, dietary change or over-the-counter laxatives as effective long-term therapy for patients with chronic constipation. Lubiprostone is a prostaglandin-derived bicyclic fatty acid available to use for long-term treatment of constipation. Lubiprostone works by increasing intraluminal chloride ion secretion, which results in a passive influx of water and sodium, leading to increased intestinal peristalsis and colonic laxation with decreased intestinal stool transit time. Randomized, double-blind, placebo-controlled trials of lubiprostone in patients with chronic constipation, irritable bowel syndrome and opioid-induced constipation have shown it to be effective and free of serious adverse effects. The most common side effects associated with lubiprostone are mild to moderate nausea and diarrhea. Currently lubiprostone is approved for treatment of chronic constipation and opioid-induced constipation for men and women at 24 µg twice daily and for treatment of irritable bowel syndrome with constipation in women at 8 µg twice daily. Additional research continues to shed light on the molecular mechanisms of lubiprostone and further work may expand its clinical applications.